Factors influencing nightly activity of deer mice (Peromyscus maniculatus) in tallgrass prairie - Rehmeier, Ryan L. (Kansas State University, 2005)
Little is known about nightly activity patterns of nocturnal small mammals under natural conditions, and how these activity patterns might be affected by photoperiod, season, and sex, age, and reproductive status of individuals. The main objectives of this research were: 1) to find an appropriate method for marking individual deer mice (Peromyscus maniculatus) so that their activity could be monitored remotely; 2) to design a portable activity-monitoring system to investigate temporal patterns of shelter use by deer mice under natural conditions; 3) to determine the influence of environmental conditions such as photoperiod and season on nightly activity of deer mice; and 4) to compare effects of demographic or physiological factors such as sex, age, and reproductive status on nightly activity of deer mice at artificial burrows in tallgrass prairie. In general, commencement of activity was correlated positively with timing of sunset, and time of retirement to the burrow was correlated positively with sunrise. Among adults, males first emerged from the burrow earlier and made more trips of shorter duration in a night than did females, although total duration of trips was similar. Return visits and subsequent stays typically were shorter for males than females, but total time spent in the burrow and retirement time relative to sunrise were similar for both sexes. Young deer mice emerged significantly later, made more trips of shorter duration, spent less total time outside, and retired to their burrow earlier than adults. Reproductive females emerged later, made fewer trips of generally longer duration, and spent shorter total amounts of time away from the burrow each night than non-reproductive females. Return visits of reproductive females were of longer duration than non-reproductives, but total time spent inside and time of retirement for the night did not differ relative to reproductive status. From parturition through lactation, activity of females showed a number of directional trends. Results suggest that under natural conditions, activity patterns of deer mice are highly variable but responsive to both the changing physical environment and internal conditions related to sex-specific maximization of fitness.
Keywords: Activity-monitoring system; PIT tag; Kansas; Reproduction; Nocturnal; Rodent; Biology, Ecology (0329); Biology, Zoology (0472)